PROBLEMS ENCOUNTERED BY FEMALE EMPLOYEES IN 5 STAR HOTELS IN ISTANBUL - Şen, Mustafa Lütfi; Üstün, Muhammed; Bozkurt, Emre; Zengin, Burhanettin (Journal of Gastronomy Hospitality and Travel - JOGHAT, 2021)
Employment, which is an indispensable element of economic and social life, has become an important issue that should be emphasized by all countries of the world. The importance of women's employment in the economy of every country is increasing. Women, who have positive contributions to both society and the economy, have achieved their current position in the business world as a result of various struggles. However, this struggle is not over yet and it is observed that it continues in different ways. This study aims to identify the problems experienced by women in accommodation establishments and to offer possible solutions to these problems. The population of the study consists of 5-star hotel businesses operating in Istanbul. During the study period, 224 employees could be reached as a sample due to the Covid-19 Pandemic. The data obtained by the survey technique were subjected to frequency and chi-square analysis with the help of SPSS statistical analysis program. Many different results were obtained in the research. The most important of these results is that women are discriminated against in the recruitment process of enterprises. Therefore, it can be concluded that women have more difficulties in planning their careers. The duties and responsibilities attributed to women make women's business lives more difficult. In the light of these results, various suggestions were tried to be made within the scope of the study.
Keywords: 5. Gender equality; 8. Economic growth; 10. No inequality